Fodder cutter (Tokka) injuries; a preventable morbidity - Danish Ali; Muhammad Adeel kaiser; Muhammad Imran khokhar; Anwer Zeb; Hassan Zaheer; Muhammad Farooq Afzal (Journal of the Pakistan Medical Association, 2020)
Pakistan is an agricultural country where fodder cutter (Tokka) is a commonly used machine on the farms. While using it, farmers often meet with accidents causing injuries which are disastrous, and mainly involve the young generation often causing lifelong disability. This is a hospital-based case series, conducted from June 2018 to January 2019 in the Department of Surgery, Lahore General Hospital, Lahore. For this study the patient’s demographic data, site of injury, procedure performed and post-operative outcome were recorded. The study includes a total of 30 cases of tokka injury, (23 males and 07 females) with median age of 25 years. Most commonly injured part of the body was the upper limb, in 26 patients, while the lower limb was involved in 2 patients. There were 18 amputations, Continuous...